Estudo neuropsicológico e de neuroimagem estrutural da apatia e cognição social na demência frontotemporal e na doença de Alzheimer - Luciano Inácio Mariano (2023)
Apathy is one of the main neuropsychiatric changes in dementia and affects different behavioral dimensions, such as motor, emotional and cognitive. The occurrence of apathy hinders the differential diagnosis between the different causes of dementia. The main objective of this thesis is to investigate the interface between apathy and social cognition in the behavioral variant of frontotemporal dementia (bvFTD) and Alzheimer's disease (AD), also investigating their neural correlates. In this work, patients with bvFTD, AD and cognitively healthy controls were included. The groups were matched by age, sex, education and disease duration (in the case of patients). All subjects were submitted the neuropsychological assessment and 3 Tesla magnetic resonance imaging (MRI). Apathy was assessed using the Starkstein Apathy Scale (SAS). In STUDY 1, 22 bvFTD patients, 20 AD patients and 23 controls were included. The objective was to determine the diagnostic accuracy (DFTvc vs. AD) of the reduced version of the Socio-Emotional Cognition Battery (“Mini-SEA”) in the presence of apathy. The results enjoyed good accuracy for the differential diagnosis between AD and bvFTD (AUC = 0.87), regardless of apathy. STUDY 2 investigated the neural correlates of apathy. Images were processed using the FreeSurfer program and cortical thickness data were acquired for 68 brain regions. The measures were correlated with the SAS score in a regression model. In AD, the multivariate linear regression model found that the left entorhinal cortex (F(1,31) = 5.17; p = 0.030; R2 = 0.527) was the only region statistically associated with apathy. The model for bvFTD identified more regions that statistically complied with the apathy score, namely: right lateral orbitofrontal cortex (F(1.30) = 5.69; p=0.009; R2=0.804), right rostral anterior cingulate cortex (F(1.29) = 4.96; p=0.003; R2=0.856); left lateral orbitofrontal cortex (F(1.28) = 4.68; p=0.042; R2=0.877), left precentral gyrus cortex (F(1.27) = 4.35; p=0.027; R2= 0.897), and the left post-central gyrus cortex (F1.26) = 3.99; p=0.019; R2=0.917). These results demonstrate that the same concept or symptom is associated with multiple brain regions, which reinforces its multidimensionality.